The impact of work-related psychosocial factors on the health and work ability of municipal transit agents - Aldo Pacheco Ferreira; Ana Paula Carneiro Carvalho (Universidade de Fortaleza, 2016)
Objective: To analyze the impact of work-related psychosocial factors on the health and work ability of municipal transit agents. Methods: A cross-sectional study was carried out with a sample of 118 subjects at the municipality of Rio de Janeiro, Rio de Janeiro State, Brazil, during 2014. They answered two questionnaires: Work Ability Index - WAI and Copenhagen Psychosocial Questionnaire - COPSOQ. These questionnaires collected information regarding how well a worker is able to perform his or her work; and on the psychosocial factors related to their work, health status, and welfare. The statistical analyses were carried out using the calculation of central tendency and dispersion measures. Results: The analysis of objectivity, acceptance, practicability, sensitivity and content validity of the questionnaires as a whole did not show any problematic result, with some limitations regarding their length. A significant association between WAI and COPSOQ was observed. The prevalence of good capacity for work was among the subjects aged between 31 and 50 years (p=0.012). However, concerning the job satisfaction, 28 (23.73%) denoted being satisfied, 74 (62.71%) partly satisfied, and 16 (13.56%) were dissatisfied. The ability index was 36.8 points, and the prevalence of good capacity for work was 76.27%. Conclusion: The results revealed that better physical and mental health are associated with greater work ability, representing that, the better the worker's health, the greater his work ability. The psychosocial work environment and, especially, the decision-making autonomy were thus important determinants of self-rated quality of life in this group of transit agents.